The eltor cholera epidemic in Dhaka in 1974 and 1975 - Khan, Moslem Uddin (1983)
Surveillance of hospitalized cholera cases from 1970 to 1977 in Dhaka, a matched control study in 1974, and a neighbourhood control study in 1975 were carried out and show a change from classical cholera to the eltor biotype during this period. Of all the hospitalized cholera cases, 9.1% in 1972 and 99.9% in 1973 were due to the eltor biotype. In 1974 and 1975 the distribution of eltor cholera cases in the city was uniform, except for areas with modern sanitation whose residents were spared. The incidence rates of cholera per 1000 infants (under the age of 1 year) were 1.16 and 0.93 for 1974 and 1975, respectively. On the whole, children below 10 years and females between 15 and 44 years of age were the ones most affected with eltor cholera. Higher rates of diarrhoea and hospitalization were noted among the contacts with cholera cases, compared with non-cholera controls. Contracting cholera was significantly associated with eating in places away from home, especially at charitable feeding centres.